English words: History and structure - Stockwell, Robert P (Cambridge University, 2013)
This book introduces some of the basic principles of linguistic analysis and is a helpful manual for vocabulary discernment and enrichment. Exercises to accompany each chapter and further readings on recent loans and the legal and medical vocabulary of English are available online.